2009
DOI: 10.1021/nl803524s
|View full text |Cite
|
Sign up to set email alerts
|

Method for Suppression of Stacking Faults in Wurtzite III−V Nanowires

Abstract: The growth of wurtzite GaAs and InAs nanowires with diameters of a few tens of nanometers with negligible intermixing of zinc blende stacking is reported. The suppression of the number of stacking faults was obtained by a procedure within the vapor-liquid-solid growth, which exploits the theoretical result that nanowires of small diameter ( approximately 10 nm) adopt purely wurtzite structure and are observed to thicken (via lateral growth) once the axial growth exceeds a certain length.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
180
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(187 citation statements)
references
References 31 publications
6
180
0
Order By: Relevance
“…6 While bulk InAs crystallizes in cubic zinc-blende structure, it has been demonstrated that InAs nanowires can be grown in the wurtzite form. [7][8][9][10] In this paper, we use first-order polarized Raman scattering and resonant Raman scattering to investigate single InAs nanowires. First-order polarized Raman scattering have been recently used to investigate GaN, 11,12 GaAs, 13,14 GaP, 15 ZnO, 16 RuO 2 , 17 and CdS (Ref.…”
Section: Introductionmentioning
confidence: 99%
“…6 While bulk InAs crystallizes in cubic zinc-blende structure, it has been demonstrated that InAs nanowires can be grown in the wurtzite form. [7][8][9][10] In this paper, we use first-order polarized Raman scattering and resonant Raman scattering to investigate single InAs nanowires. First-order polarized Raman scattering have been recently used to investigate GaN, 11,12 GaAs, 13,14 GaP, 15 ZnO, 16 RuO 2 , 17 and CdS (Ref.…”
Section: Introductionmentioning
confidence: 99%
“…32-34 With a judicious optimization of growth conditions, single NWs with a pure zinc-blende or wurzite structure can be obtained. [35][36][37] Still, the optical and electronic properties tend to fluctuate considerably from NW to NW, 2 which precludes the proper control of the response of an ensemble of nanowires.…”
Section: Introductionmentioning
confidence: 99%
“…32-34 With a judicious optimization of growth conditions, single NWs with a pure zinc-blende or wurzite structure can be obtained. [35][36][37] Still, the optical and electronic properties tend to fluctuate considerably from NW to NW, 2 which precludes the proper control of the response of an ensemble of nanowires.Recently, alternative approaches to obtain defect-free nano structures have been proposed. Particularly promising is the inversion of polarity from B to A as well as template assisted and nano-membrane assisted selective epitaxy (TASE and MASE, respectively).…”
mentioning
confidence: 99%
“…Among the indirect band gap III-V semiconductors with zinc blende (ZB) crystal structure, GaP is predicted to become a direct band gap material when grown with wurtzite (WZ) crystal structure. [1][2][3][4][5] Semiconductor nanowires (NWs) have shown excellent control of the growth of ZB-WZ phases, [6][7][8][9] allowing crystal structure band engineering. [10][11][12] Recently, the Auseeded growth of high purity WZ GaP nanowires via vaporliquid-solid (VLS) method was demonstrated, and the optical properties have been investigated.…”
Section: Introductionmentioning
confidence: 99%